Relationships Among 10-Year Fracture Risk Assessment, Comorbidity Burden, and Functional Status in Ischemic Stroke Survivors - İlknur Aykurt Karlıbel; Meliha Kasapoğlu Aksoy (Galenos Yayinevi, 2022)
Objective:Poststroke disabilities and comorbidities pose serious problems among the stroke survivors. We thought that the comorbidity burden and functional status may impact determining the fracture risk of patients with ischemic stroke. The aim of this study was to investigate the effect of comorbidity burden and functional status in determining the 10-year fracture risk of patients with ischemic strokes.Materials and Methods:The cross-sectional study included 138 ischemic stroke survivors. Functional status [Functional Independence Measure (FIM)], comorbidity burden [Charlson Comorbidity index (CCI)] and fracture risk [The Fracture Risk Assessment Tool (FRAX)] were evaluated.Results:The median age of the cases was 64 (49-83) years (53.6% male). As the CCI increased, motor (FIM-motor) and cognitive (FIMcognitive) functions decreased. The decrease in FIM-motor and FIM-cognitive and the increase in the CCI increased statistically significantly the risk of major osteoporotic fracture (FRAX-MOFR) and hip fracture (FRAX-HFR) (p<0.05). The patients with a history of osteoporotic fractures were older, had lower FIM-motor and FIM-cognitive, and higher CCI (p<0.05). There was a significant relationship between FIM-motor, FIMcognitive, and CCI, and FRAX-MOFR and FRAX-HFR. CCI was the independent variable.Conclusion:In stroke survivors, levels of the motor and cognitive functions and comorbidity burden could predict the risk of hip and major osteoporotic fractures. Comorbidity burdens are independent variables.